Interactive Regulation of Hormone and Resistance Gene in Proline Metabolism Is Involved in Effector-Triggered Immunity or Disease Susceptibility in the Xanthomonas campestris pv. campestris–Brassica napus Pathosystem - Mamun, Md Al; Islam, Md Tabibul; Lee, Bok-Rye; Bae, Dong-Won; Kim, Tae-Hwan (Frontiers in Plant Science, 2022)
To characterize cultivar variations in hormonal regulation of the transition between pattern-triggered immunity (PTI) and effector-triggered immunity or susceptibility (ETI or ETS), the responses of resistance (R-) genes, hydrogen peroxide, and proline metabolism in two Brassica napus cultivars to contrasting disease susceptibility (resistant cv. Capitol vs. susceptible cv. Mosa) were interpreted as being linked to those of endogenous hormonal levels and signaling genes based on a time course of disease symptom development. Disease symptoms caused by the Xanthomonas campestris pv. campestris (Xcc) infections were much more developed in cv. Mosa than in cv. Capitol, as shown by an earlier appearance (at 3 days postinoculation [3 DPI]) and larger V-shaped necrosis lesions (at 9–15 DPI) in cv. Mosa. The cultivar variations in the R-genes, hormone status, and proline metabolism were found in two different phases (early [0–3 DPI] and later [9–15 DPI]). In the early phase, Xcc significantly upregulated PTI-related cytoplasmic kinase (Botrytis-induced kinase-1 [BIK1]) expression (+6.3-fold) with salicylic acid (SA) accumulation in cv. Capitol, while relatively less (+2.6-fold) with highly increased jasmonic acid (JA) level in cv. Mosa. The Xcc-responsive proline accumulation in both cultivars was similar to upregulated expression of proline synthesis-related genes (P5CS2 and P5CR). During the later phase in cv. Capitol, Xcc-responsive upregulation of ZAR1 (a coiled-coil-nucleotide binding site-leucine-rich repeat [CC-NB-LRR-type R-gene]) was concomitant with a gradual increase in JA levels without additional proline accumulation. However, in cv. Mosa, upregulation of TAO1 (a toll/interleukin-1 receptor-nucleotide binding site-leucine-rich repeat [TIR-NB-LRR-type R-gene]) was consistent with an increase in SA and abscisic acid (ABA) levels and resulted in an antagonistic depression of JA, which led to a proline accumulation. These results indicate that Xcc-induced BIK1- and ZAR1-mediated JA signaling interactions provide resistance and confirm ETI, whereas BIK1- and TAO1-enhanced SA- and/or ABA-mediated proline accumulation is associated with disease susceptibility (ETS).